Quality of recovery after anaesthesia measured with QoR-40: a prospective observational study - Guimarães-Pereira,Luís (2016)
Abstract Background: QoR-40, a 40-item questionnaire on quality of recovery from anaesthesia, has been shown to measure health status after surgery. Our aim was to evaluate the incidence of poor quality of recovery in our Post Anaesthesia Care Unit and to compare their QoR-40 scores before surgery and 3 months later. Methods: A prospective observational study was conducted in adult patients consecutively admitted from 18 June to 12 July 2012. The follow-up period was 3 months. We exclude patients submitted to cardiac surgery, neurosurgery, obstetric surgery and with a mini-mental state examination test score lower than 25. The primary endpoint was quality of recovery measured with the validated Portuguese for Portugal version of the QoR-40 before surgery (T0), 24 h after surgery (T1) and 3 months after (T2). Results: A total of 114 patients completed the study. Mean QoR-40 score was 169 and patients with poor quality of recovery were identified if their QoR-40 score was lesser than 142. This occurred in 26 patients (24%). Global median scores for patients with poor quality of recovery were lower at T0 (121 vs. 184, p < 0.001), at T1 (120 vs. 177, p < 0.001) and at T2 (119 vs. 189, p < 0.001). Conclusion: Patients with poor quality of recovery had lower quality of life. This fact may allow earlier and more effective interventions, in order to improve quality of life after surgery. Beside its utility after surgery, QoR-40 may be important prior to surgery to identify patients who will develop a poor quality of recovery.